Environmental Microbiology - Environmental Microbiology (Wiley, 2026)
Environmental Microbiology is devoted to the advancement of our understanding of microbial interactions and microbial processes in the environment and publishes cutting-edge original research reporting significant advances in or relating to this subject.
FI 1
Q2
Keywords: Life Sciences; Microbial Ecology; Ecología microbiana; Acuerdos transformativos; Transformative agreements; Procesos microbianos; Comunidades microbianas; Genética; Microorganismoa